1948
DOI: 10.1002/zaac.19482560501
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen im System CaOP2O5SiO2

Abstract: Die Gleichgewichte im kalkreichen Teil des Systems CaOP2O5SiO2 wurden thermisch, röntgenographisch und mikroskopisch untersucht. Im binären Randsystem CaO2O5 schmilzt die Verbindung 4 CaO · P2O5 unter Abspaltung von CaO. Der Schnitt 2 CaO · SiO2  3 CaO · P2O5 ist dadurch gekennzeichnet, daß mehrere Mischkristallreihen auftreten. Der Silikocarnotit bildet sich erst durch Reaktion im festen Zustand. Der kalkreiche Teil des ternären Systems wird durch die große Fläche der primären Ausscheidung von CaO beherrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1949
1949
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…The thermal decomposition of dibasic calcium orthephosphate to ~/-Ca2P207 is apt to be rather complex depending on whether CaHPO4.2H20 or crystalline CaHPO~ is the starting material and whether the ambient atmosphere is dry or humid (8)(9)(10)(11). The transition temperature for the inversion of fl-Ca2P207 to ~-Ca2P20~ is given as 1140 ~ (16), 1270 ~ (17), 1130 ~ (18), and 1220 ~ (15). W h e n ~-CauP207 is fired at a somewhat higher temperature ~-Ca2P207 is produced.…”
Section: Journal Of the Electrochemical Societymentioning
confidence: 99%
“…The thermal decomposition of dibasic calcium orthephosphate to ~/-Ca2P207 is apt to be rather complex depending on whether CaHPO4.2H20 or crystalline CaHPO~ is the starting material and whether the ambient atmosphere is dry or humid (8)(9)(10)(11). The transition temperature for the inversion of fl-Ca2P207 to ~-Ca2P20~ is given as 1140 ~ (16), 1270 ~ (17), 1130 ~ (18), and 1220 ~ (15). W h e n ~-CauP207 is fired at a somewhat higher temperature ~-Ca2P207 is produced.…”
Section: Journal Of the Electrochemical Societymentioning
confidence: 99%
“…This polymorphic form of TCP does not get overcooled, even in the course of quenching, and its presence can be detected only during high‐temperature XRD experiments. TCP melts congruently at 1810°C …”
Section: Introductionmentioning
confidence: 99%
“…The phosphate was prepared in a solid state by the ceramic method according to method proposed in [42]. In this synthesis route, a stoichiometric mixture of CaCO 3 4 . The chemical composition of samples under study is shown in the Tab.…”
Section: Synthesismentioning
confidence: 99%
“…The temperature and composition of eutectic points, as well as the melting point of Ca 3 Y(PO 4 ) 3 have been adopted from [34]. The melting point of Ca 3 (PO 4 ) 2 has been taken from [3].…”
Section: Thermal Behavior Of Ca 3 Y(po 4 )mentioning
confidence: 99%
See 1 more Smart Citation